On Beta-Prime Submodules - Khumprapussorn, Thawatchai (IndoMS, 2019)
We introduce the concepts of β-prime submodules and weakly β-prime submodules of unital left modules over a commutative ring with nonzero identity. Some properties of these concepts are investigated. We use the notion of the product of two submodules to characterize β-prime submodules of a multiplication module. Characterization of β-prime and weakly β-prime submodules of arbitary modules are also given.